Development of influential factors framework of unethical behaviour among working young adults - Tengku Intan Nabilah, Tenku Sulaiman; Fatimah, Mahmud; Hasnah, Haron (Universal Publishers, 2023)
Unethical behaviour among working young adults is the greatest challenge in today’s society, as the young adults of today are the leaders of the future. Thus, it shows how important to build up first class human capital with good values and it starts by educating young adults. However, due to limited studies, the existing literature yet to provide sufficient explanation of the contributing factors to unethical behaviour amongst working young adults especially in developing countries like Malaysia. Hence, this study introduces the conceptual framework to clarify the factors that influence unethical behaviour intention. Theory of planned behaviour (TPB) and Fraud diamond theory (FDT) were described briefly in this study to explain the factors. The study suggest that the most appropriate data collection technique for this conceptual framework is through questionnaires. Further, this study will develop a common ethical scenario to measure unethical behaviour based on the definition of unethical behaviour applicable in Malaysia. It is hoped that this conceptual framework can be seen in terms of practice which will be beneficial to regulators such as Malaysian Anti- Corruption Commission (MACC), The National Centre for Governance, Integrity and Anti-Corruption (GIACC), The Malaysian Institute of Integrity (IIM) as well as the Institute for Youth Research Malaysia.